Assessing water loss and sediment deposition at Mavrokolympos Dam using multimodal methods: TLS, UAV, and satellite imagery - Christofi, Demetris A.D.; Evagorou, Evagoras S.; Mettas, Christodoulos; Stylianou, Neophytos; Hadjimitsis, Diofantos G. (My University, 2025)
The climate zone of Cyprus is characterized as semi-arid climate followed by hot, dry summers and mild winters with low rainfall. For addressing water scarcity during the dry summer months, the Cypriot government implemented a policy of constructing reservoir dams across the island. Most of these dams were built after 1960 and are now ageing. The sudden water evacuation of the Mavrokolympos Dam in Paphos, Cyprus, due to a ventilating system failure provided a rare opportunity to assess rapid water loss and sediment transport within the reservoir over time and the outflow sentiment volume during the water loss event. This study integrates terrestrial laser scanning (TLS), unmanned autonomous vehicles (UAVs), and a time series of PlanetScope satellite images to analyze pre- and post-evacuation conditions focusing on the initial water body mass just before and immediately after the event occurred. The satellite images were used to delineate the waterbody's extent before and after drainage, enabling volume estimation of the water loss. TLS and UAV surveys captured high-resolution topographic data of the emptied reservoir, validating satellitederived volume estimations through a Digital Elevation Model (DEM). Additionally, the sediment layer deposition in the reservoir was quantified providing insights into the waterbody mass of the dam at full capacity in recent years, also allowing for an assessment of sediment displacement towards the river mouth. This multimodal approach enhances our understanding of reservoir dynamics, water resource management, and sediment transport processes following abrupt drainage events.
Keywords: Dam; water; TLS; UAV; PlanetScope; Cyprus